2020
DOI: 10.1515/bmc-2020-0017
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide: A Promising Material for Regenerative Medicine and Tissue Engineering

Abstract: Regenerative medicine and tissue engineering have been considered pioneer fields in the life sciences, with an ultimate goal of restoring or switching lost or impaired body parts. Graphene oxide (GO) is the product of graphene oxidation and presents a great opportunity to make substantial progress in the field of regenerative medicine; for example, it supports the possibility of creating a cellular niche for stem cells on a nanoparticle surface. GO creates a fascinating structure for regulating stem cell behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 100 publications
0
34
0
Order By: Relevance
“…Its versatility and tunable compatibility with robust and diverse materials captivated the focus in the research on skin [ 17 ] and adipose [ 18 ] regeneration, muscle (cardiac and skeletal [ 19 ]) engineering, nerve [ 20 ], as well as de novo cartilage and bone tissue [ 21 ]. GO demonstrated excitingly good interaction with many kinds of cell types, such as stem cells [ 22 , 23 ], neural cells [ 24 , 25 ], cardiomyocytes [ 26 ] and endothelial [ 27 ] cells and osteoblasts [ 28 ], while the non-toxic effect of GO-reinforced materials has been numerously reported in both in vitro and in vivo experimental conditions [ 29 , 30 ]. Even though there is not a global consensus on the drawbacks that GO additivities can be associated with, many results support that the impact of GO in the osteogenic development is rather positive, as long as the concentration of GO is not very high (~0.5 wt.%) [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its versatility and tunable compatibility with robust and diverse materials captivated the focus in the research on skin [ 17 ] and adipose [ 18 ] regeneration, muscle (cardiac and skeletal [ 19 ]) engineering, nerve [ 20 ], as well as de novo cartilage and bone tissue [ 21 ]. GO demonstrated excitingly good interaction with many kinds of cell types, such as stem cells [ 22 , 23 ], neural cells [ 24 , 25 ], cardiomyocytes [ 26 ] and endothelial [ 27 ] cells and osteoblasts [ 28 ], while the non-toxic effect of GO-reinforced materials has been numerously reported in both in vitro and in vivo experimental conditions [ 29 , 30 ]. Even though there is not a global consensus on the drawbacks that GO additivities can be associated with, many results support that the impact of GO in the osteogenic development is rather positive, as long as the concentration of GO is not very high (~0.5 wt.%) [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among all their potential functions, GO- and rGO-based scaffolds have particularly attracted attention because of their great clinical projection in tissue regeneration therapies, making them very promising candidates in this field ( Table 1 ). Both GO and rGO have shown a strong impact on the proliferation and differentiation of implemented stem cells when applied on 3D scaffolds in bones, cardiac and neural regenerative medicine, skin and adipose tissues [ 20 ]. It has been reported that nano-GO incorporation in nanofibrous scaffolds, made of polycarbonate diol and isosorbide-based polyurethane, enhances the initial adhesion and spreading of myoblasts along with upregulation of myosin heavy chain mRNA levels.…”
Section: Biomedical Applications Of Gomentioning
confidence: 99%
“…GOs are a derivative of graphene monolayer with many groups containing oxygen atoms such as hydroxyl and epoxy functional groups, which are located on the surface of the GOs, and carboxyl groups that appear on the edges of the GO flake. The GO oxidation state enables obtaining substrates with appropriate physico-chemical properties for cell culturing [ 74 ]. Thanks to the presence of functional groups, the GO and rGO scaffolds gain hydrophilicity and water solubility.…”
Section: Two-dimensional Graphene-based Scaffoldsmentioning
confidence: 99%